Effect of Political Will Perception and Executive Job Satisfaction Toward Managerial Performance - RIFA'I, AHMAD; Tan, Syamsurijal; Edward, Edward; Adriani, Zulfina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study aims to determine the effect of executive job satisfaction on managerial performance through political will perception, to determine the effect of political will perception on managerial performance and to determine the effect of executive job satisfaction on managerial performance. Methodology/approach – A This research is a quantitative research using WarPls 07 to process the data. This research was conducted at the Government of Indragiri Hilir Regency, Riau Province, Indonesia. The sampling technique used is probability sampling with proportionate stratified random sampling. The sample was calculated using the Herry King Nomogram Table with an error rate of 5% where 135 respondents were selected. Findings – It Test results The effect of executive job satisfaction on managerial performance has a beta coefficient of 0. 272 and a p value of <0.001. Thus it can be concluded that executive job satisfaction has a positive effect on managerial performance. The effect of political will perception on managerial performance has a beta coefficient of 0.389 and a p value of <0.001. Thus, it can be concluded that the political will perception has a positive effect on managerial performance. Testing the effect of executive job satisfaction on the political will perception has a beta coefficient of 0.633 and a p value of <0.001. Thus, it can be concluded that executive job satisfaction has a positive effect on political will perception. Testing the effect of executive job satisfaction on managerial performance through the political will perception has a beta coefficient of 0.246 with a p value <0.001 which is smaller than the sig level of 0.05. Novelty/value – As executive job satisfaction increases managerial performance through the political will perception and its effect is significant. Thus, it can be concluded that the political will perception can mediate the effect of executive job satisfaction on managerial performance